Spatial distribution of PM1 and sinus arrhythmias in Athens, Greece - Grigoropoulos, K. N.; Nastos, P. T.; Ferentinos, G.; Gialouris, A.; Vassiliou, T.; Mavroidakos, J.; Avgeri, D.; Kalabokis, V.; Saratsiotis, D. (Fresenius Environmental Bulletin, 2008)
The study of particulate matter with diameter less than 1 μm (PM 1) in Athens' atmosphere and their impacts on human health is the goal of this study. PM1 concentrations were recorded by three detectors (light scattering method) at six vital points in high traffic peak roads, during the period 1/10/2006-30/9/2007. The collected PM1 samples concern the same hour of the day, in absence of wind. The spatial distributions of the PM1 concentrations for the warm (April to September) and the cold (October to March) period of the year were achieved by the use of Kriging method. Further to, in order to find out the impacts of PM1 concentrations on health, we analyzed daily admissions for non-fatal arrhythmias to emergency units of the Social Security Institute and a Regional Hospital of Athens. Results demonstrate a significant relationship of PM1 with sinus arrhythmias, which confirms the assumption that PM1 represent one of the main hazards in cardio respiratory syndromes in the most polluted cities of Europe, which confront high traffic problems, due to the enormous number of exhausts emissions.
Keywords: Athens; Athens [Attica]; Attica; cardiovascular disease; concentration (composition); Eurasia; Europe; Greece; health impact; hospital sector; kriging; Particulate matter; PM1 concentrations; pollution effect; pollution exposure; road transport; Sinus arrhythmias; Southern Europe; Spatial distribution; urban pollution